Pengaruh Model Pembelajaran Project Based Learning (PjBL) Berbantuan GeoGebra Terhadap Kemampuan Literasi Matematis Siswa - Wulandari, Widia; Kurniawati, Lia; Otong Suhyanto (Pusat Studi Pengembangan Pembelajaran Matematika, 2025)
Mathematical literacy is one of the abilities that students must have. Mathematical literacy skills include the ability to use, create, review, and utilize information to solve problems based on their mathematical knowledge and skills. This study aims to analyze the effect of Project Based Learning learning model assisted by GeoGebra on students' mathematical literacy skills. This research was conducted at one of the public junior high schools in Bekasi in the 2024/2025 school year. The research method used is Quasi Experimental Design with posttest control group design. The sample used consisted of 34 experimental class students and 34 control class students. Data collection on mathematical literacy skills using test instruments in the form of eleven description questions that have been tested for validity, reliability, differentiating power, and difficulty level. The indicators of mathematical literacy skills studied were formulate, employ, and interpret. The results showed that the mathematical literacy skills of students taught with the GeoGebra-assisted Project Based Learning learning model were higher than the mathematical literacy skills of students taught with the Direct Instruction model. In addition, the results of this study indicate that the GeoGebra-assisted Project Based Learning model can be recommended to facilitate students' mathematical literacy skills.